Heat shock protein 60 levels in tissue and circulating exosomes in human large bowel cancer before and after ablative surgery. Issue 18 (8th June 2015) - Campanella, Claudia; Rappa, Francesca; Sciumè, Carmelo; Marino Gammazza, Antonella; Barone, Rosario; Bucchieri, Fabio; David, Sabrina; Curcurù, Giuseppe; Caruso Bavisotto, Celeste; Pitruzzella, Alessandro; Geraci, Girolamo; Modica, Giuseppe; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Heat shock protein 60 (Hsp60) is a chaperonin involved in tumorigenesis, but its participation in tumor development and progression is not well understood and its value as a tumor biomarker has not been fully elucidated. In the current study, the authors presented evidence supporting the theory that Hsp60 has potential as a biomarker as well as a therapeutic target in patients with large bowel cancer. METHODS The authors studied a population of 97 subjects, including patients and controls. Immunomorphology, Western blot analysis, and quantitative real‐time polymerase chain reaction were performed on tissue specimens. Exosomes were isolated from blood and characterized by electron microscopy, biochemical tests, and Western blot analysis. RESULTS Hsp60 was found to be increased in cancerous tissue, in which it was localized in the tumor cell plasma membrane, and in the interstitium associated with cells of the immune system, in which it was associated with exosomes liberated by tumor cells and, as such, circulated in the blood. An interesting finding was that these parameters returned to normal shortly after tumor removal. CONCLUSIONS The data from the current study suggested that Hsp60 is a good candidate for theranostics applied to patients with large bowel carcinoma and encourage similar research among patients with other tumors in which Hsp60 has been implicated. Cancer 2015;121:3230–3239. © 2015 American Cancer Society.